Embedding Digital Literacies in English Language Teaching: Students' Digital Video Projects as Multimodal Ensembles. Issue 4 (5th September 2013) - Hafner, Christoph A.
<x xml:space="preserve">Abstract</x> As a result of recent developments in digital technologies, new genres as well as new contexts for communication are emerging. In view of these developments, this article argues that the scope of English language teaching be expanded beyond the traditional focus on speech and writing to the production of multimodal ensembles, drawing on a range of other semiotic modes. The article describes an undergraduate course in English for science at a university in Hong Kong, which incorporated elements of digital literacies. Students were engaged in a project to conduct a simple scientific experiment, reporting their findings (1) as a multimodal scientific documentary, shared through YouTube with a general audience of nonspecialists, and (2) as a written lab report aimed at a specialist audience. This article focuses on the multimodal scientific documentaries created by students and evaluates their potential in terms of language learning by drawing on data from student interviews, student comments on a course blog, and the students' documentaries themselves. The analysis shows that students met the challenge of writing for an authentic audience by combining a range of modes (with language playing an important role) to develop an effective rhetorical "hook" and appropriate discoursal identity in their efforts to appeal to their audience.